Systematics, natural history, and hemipenial morphology of Dendrophidion brunneum (Günther) (Serpentes: Colubridae), a poorly known snake from the Andes of Ecuador and Peru - Cadle, John E. (Zootaxa, 2010)
Systematic characters, distribution, natural history, and hemipenial morphology are described for Dendrophidion brunneum (Günther), a poorly known snake from Ecuador and Peru. It has 17 midbody scale rows; 145–165 ventrals; 135–158 subcaudals; a tail 38–44% of total length; a relatively uniform green to brown dorsum; and a maximum length of 1370 mm (700–800 mm SVL). The species occurs from northern Ecuador to 8° S latitude in Peru, primarily on the Pacific slopes of the Andes but with a few documented lowland localities in Peru. Dendrophidion brunneum is diurnal, terrestrial, heliophilic, and oviparous. It occurs in humid montane forests or mixed puna grassland/highland forest. Recorded prey are small terrestrial frogs but a large individual possibly consumed a lizard. Defensive mechanisms include a pseudautotomic tail and behaviors such as striking, biting, and neck inflation. The hemipenis has a short, narrow base, a greatly expanded distal region, and a simple, centrolineal sulcus spermaticus. The expanded region is ornamented with spines, distal to which two flounces completely encircle the organ and another extends partially around one side. The flounces are unusual in being thin, membranous structures and in having mineralized rods (reduced spinules) completely embedded within the membranes. The apex is nude except for a few vestigial calyces. Unusual hemipenial characters are discussed.